Green Growth Policies and Sustainable Economic Growth in South Africa: An Autoregressive Distributed Lag and Toda‑Yamamoto Approach - Oyebanji, Ibitoye J.; Khobai, Hlalefang; Le Roux, Pierre (International Journal of Energy Economics and Policy, 2018)
This paper investigates the long-run or sustainability effect and the causal relationship between green energy consumption, gross capital formation, gross domestic product (GDP), energy import and fuel export for South Africa between 1984 and 2015. The study adopts the bound testing approach to cointegration to check the long-run relationship, and the Toda-Yamamoto approach to determine the direction of causality. Results, indicate a positive unidirectional relationship between changes in green growth policies and gross capital formation. This finding suggests that adopting green growth policies lead to increased investments. In contrast, green growth was found to have a negative effect on GDP and absence of causality. The findings indicate a boost in the balance of payment as evidenced by the positive long-run relationship between green growth policies and fuel exports. Therefore, the study suggests the adoption and continued implementation of green growth policies in developing countries such as South Africa. Keywords: Green Growth, Sustainable Economic Growth, Energy Imports, Fuel Exports, South Africa JEL Classification: QO2 DOI: https://doi.org/10.32479/ijeep.6563